Analisis Performansi Dua Sistem Operasi Server CentOS 8 dan Oracle Linux 8 Menggunakan Metode Levene Dengan SysBench - Gde Andrayuga Pramaditha Tenaya; I Dewa Putu Gede Wiyata Putra; Anak Agung Gde Ekayana; I Gusti Made Ngurah Desnanjaya; Anak Agung Gede Bagus Ariana (INFORMAL: Informatics Journal, 2022)
CentOS 8 is a popular operating system for servers, but will discontinue. The Oracle Linux 8 operating system was chosen as a replacement because this operating system has many similarities with CentOS 8 and is distributed by the same party, namely RHEL (Red Hat Enterprise Linux). This study aims to compare the stability of the two server operating systems, as well as provide a reference for operating system users to choose a server operating system. CPU and memory tests were performed using SysBench software with the same number of threads, which were then recorded and compared. Cacti software is also used to compare CPU and memory performance in real time. The results showed that Oracle Linux 8 and CentOS 8 are two operating systems with different variances, although the kernels used by both operating systems are the same. Oracle Linux 8 can serve clients faster than CentOS 8 with a difference of 0.26 seconds.